Exploring the experiences of Haitians/Haitian Americans in Miami-Dade County, Florida during the COVID-19 pandemic: how this community coped with the public health emergency - Sternberg, Candice A.; Richard, Danelle; Daniel, Valerie E.; Chery, Maurice J.; Beauvoir, Maika; Marcelin, Dora; Francois, Aline; Titus, Micaelle; Mann, April; Alcaide, Maria L.; Dale, Sannisha K. (Frontiers in Public Health, 2024)
Objective-To explore and describe the experiences of Haitians/Haitian Americans in Miami-Dade County, Florida during the COVID-19 pandemic, including their attitudes and practices toward vaccination. Design-We interviewed 15 community members and 15 stakeholders in the Haitian/Haitian American community in Miami-Dade County, Florida using a semi-structured interview guide.The qualitative interviews were conducted between February 4, 2021, and October 1, 2021.They were conducted in both English and Haitian Creole, audio recorded transcribed/ translated, and coded using thematic content analysis.Results-The analyses revealed 9 major themes: (1) thoughts about the pandemic, (2) concerns about the COVID-19 vaccines, (3) healthcare access, February-October 2021, (4) intrapersonal relationship dynamics, (5) thoughts about individuals diagnosed with COVID-19, (6) thoughts about prevention measures (e.g., wearing masks, hand hygiene, social distancing, vaccination), (7) mental health struggles and coping, (8) food insecurity, and (9) overall experiences of the pandemic. The findings reveal that the COVID-19 public health emergency negatively affected Haitians/Haitian Americans across several domains, including employment, healthcare access, personal relationships, and food security.Conclusions: This research echoes the compounding negative experiences reported by multiple disadvantaged groups during the COVID-19 pandemic. From loss of employment to healthcare barriers, the pandemic forced many Haitians/Haitian Americans into greater economic and social instability. Interventions addressing these issues should recognize how these factors may interact and compound the experiences of this group. Health and public health agencies should work alongside community partners to build trust so that preventive efforts will be more readily accepted during public health emergencies.